Language and dispositive. An analysis of the TV show Dr. House as a paradigmatic case of Colombian medical practice - Clavijo Poveda, Jairo (2019)
In the framework of the Philosophy of Science and Technology, this article wants to highlight the importance of the conversion of the body into a medical language. In order to achieve this goal, we made use of the Television Show Dr. House. We selected different fragments of three episodes and, even though the cases shown by the program are not real they keep similarities with real life cases and, in this sense, are susceptible to be analyzed. We based our analysis in the agambenian notion of “dispositive” to understand the extension of medical power nowadays. A doctor, to exercise his trade, converts the living into codes, index and concepts. The diagnosis process is always a linguistic process, based on the observation by the doctor and the selection of symptoms and signs of sickness. Doctors have physical prosthesis that allow them to perceive the patient’s body in a different way that if they only depended upon their human senses, consequently they are able to convert the body into data.